Petrography of Sandston Units in Gercus Formation, Shaqlawa and Dokan areas Northern Iraq - Nusaif, Alaa K.; Khwedim, Kareem H. (Iraqi Journal of Science, 2023)
The present study deals with the petrographic investigations revealed that the sandstone of Gercus Formation the studied samples of sandstone units composed primarily of rock fragments (sedimentary, igneous and metamorphic), quartz grains (monocrystalline and polycrystalline), and feldspars (orthoclase, microcline and plagioclase). These components are cemented by carbonate and iron oxides. The studied sandstones are classified as litharenites, Sandstone rocks of Gercus Formation are chemically and mechanically unstable due to the high percentage of rock fragments ,such a grain assemblage infers that the source of the rock fragments is nearby. The petrographic analyses indicate that the studied sandstones are immature mineralogically because of high content of unstable components, such as lithic fragments and feldspars. the tectonic provenance for Gercus formation can be described as lithic recycled.